Penegakan Hukum terhadap Modifikasi Kendaraan Bermotor oleh Satuan Lalu Lintas Polres Gianyar - I Made Hadiyanta Purnama Sardi; Anak Agung Istri Agung; Ida Ayu Putu Widiati (Jurnal Konstruksi Hukum, 2021)
The rise of motorized vehicle modification can have a negative impact if there is a lack of understanding from the public, which can endanger motorists on the road. Every party who wishes to modify a motorized vehicle is required to have a permit as required in Law Number 22 of 2009 concerning Road Traffic and Transportation. The problems in this thesis are 1) what are the types of motor vehicle modifications that violate traffic regulations 2) How is the law enforcement against motorized vehicle modifications that violate the traffic regulations by the Gianyar Police Traffic Police The purpose of this research is to add insight into motorized vehicle modification in accordance with applicable regulations. This study uses an empirical method and uses a sociology of law approach. The results showed that the modification of motorized vehicles had to be subjected to a retype test, and, tit did not carry out the type test it would have violated Article 50 paragraph (1) of Law Number 22 Year 2009 concerning Road Traffic and Transportation. Then law enforcement on motor vehicle modification has been optimal, but there are still several factors that hinder enforcement.